2001
DOI: 10.1136/ard.60.10.924
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of radiographic joint damage in patients with early rheumatoid arthritis

Abstract: Objective-To determine factors at diagnosis, associated with radiographic damage at diagnosis and after one year, in patients with early rheumatoid arthritis (RA). Methods-New patients with early RA were followed up for one year. Possible prognostic factors were duration of complaints, morning stiVness, disease activity score (DAS28), functional status (Health Assessment Questionnaire (HAQ) score), rheumatoid factor (IgM RF), and C reactive protein (CRP). Outcome was defined as radiographic damage of the hands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
100
2
9

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 24 publications
13
100
2
9
Order By: Relevance
“…Adjustment for baseline levels of disease activity (DAS28 score), inflammation (ESR), RF status, and radiologic damage had virtually no influence, and increased urinary CTX-I and CTX-II levels still predicted progression with very similar odds ratios, findings that are consistent with our previous 1-year study in another population of patients with early RA (21). These relative risks were actually higher than those in the present study for the baseline DAS28 score, RF, ESR, and radiologic score, which have so far been found to be the strongest predictors of progression (6)(7)(8)(9)(10)(11). Multivariate linear and logistic regression analyses gave very concordant results and indicated that urinary CTX-I and CTX-II together with, but independent of, the ESR, RF positivity, and joint damage score, are the most important risk factors for progression.…”
Section: Prediction Of Joint Damage In Early Ra By Bone and Cartilagesupporting
confidence: 91%
See 1 more Smart Citation
“…Adjustment for baseline levels of disease activity (DAS28 score), inflammation (ESR), RF status, and radiologic damage had virtually no influence, and increased urinary CTX-I and CTX-II levels still predicted progression with very similar odds ratios, findings that are consistent with our previous 1-year study in another population of patients with early RA (21). These relative risks were actually higher than those in the present study for the baseline DAS28 score, RF, ESR, and radiologic score, which have so far been found to be the strongest predictors of progression (6)(7)(8)(9)(10)(11). Multivariate linear and logistic regression analyses gave very concordant results and indicated that urinary CTX-I and CTX-II together with, but independent of, the ESR, RF positivity, and joint damage score, are the most important risk factors for progression.…”
Section: Prediction Of Joint Damage In Early Ra By Bone and Cartilagesupporting
confidence: 91%
“…Several retrospective and prospective studies have identified potential predictors of radiographic progression (6)(7)(8)(9)(10)(11), including clinical signs of disease activity, systemic indices of inflammation, such as the erythrocyte sedimentation rate (ESR) and serum C-reactive protein (CRP) levels, rheumatoid factor (RF) positivity, presence of HLA-DRB1 genotypes, and evidence of radiographic damage. Thus, most of the current predictors are based on clinical signs of disease activity and/or inflammation or on radiographic damage.…”
mentioning
confidence: 99%
“…This study encompassed a relatively short period of observation, and the changes in radiographic progression seen over 1 year may not necessarily extrapolate to longer observation periods. However, a large body of evidence exists to support the relationship between elevated values of composite disease activity indices, ESR and CRP levels, and radiographic progression in RA patients over many years of observation (7,8,(10)(11)(12)(13)43). Moreover, our findings in the present study are similar to results of a subanalysis from the Anti-Tumor Necrosis Factor Trial in Rheumatoid Arthritis with Concomitant Therapy (ATTRACT) trial involving patients with longstanding RA (44).…”
Section: Discussionmentioning
confidence: 99%
“…While progression of radiographic abnormalities may have limited implications with regard to function in the short term, accumulation of destruction over time translates into a decline of functional capacity and quality of life (4)(5)(6). Both functional decline and radiographic progression have been strongly associated with continued disease activity as reflected by persistent elevations in swollen joint counts, the acute-phase response, or disease activity scores derived from composite indices (4,(6)(7)(8)(9)(10)(11)(12)(13). These relationships have been established from previous studies of the natural course of RA and from results of clinical trials of treatments that are no longer the standard of care (14)(15)(16).…”
mentioning
confidence: 99%
“…Patients who fail to enter clinical remission can have significant levels of ongoing inflammation, despite meeting currently accepted treatment response criteria (4,7). Other prognostic factors, including the presence of rheumatoid factor, rheumatoid nodules, HLA-DR4/ shared epitope, and anti-cyclic citrullinated peptide antibodies (9)(10)(11)(12), are associated with worse outcomes when using grouped data, but they are not useful in predicting individual outcomes or responses to therapy. New biomarkers are therefore needed that can predict and be used to help prevent long-term radiographic progression in individual patients.…”
mentioning
confidence: 99%